Methodology of Management Strategy Changes for Digitalization of Business Processes for Community Services in Indonesia - Kartono Kartono; Nabaraj Bhowmik; Andri Hermawan (Jurnal Ekuisci, 2026)
Background. Digital transformation in the public sector in Indonesia is a strategic need to improve the quality of public services. Purpose. This research aims to analyze change management strategies in the digitalization of business processes and their impact on the effectiveness of public services. Method. The research methodology uses a qualitative approach with literature studies and policy analysis. Results. The results of the study show that the success of digital transformation is influenced by leadership, organizational readiness, technological infrastructure, and community participation. Implementation. This research provides strategic recommendations for government agencies in implementing digitalization effectively.